2019
DOI: 10.1038/s41586-019-1793-z
|View full text |Cite
|
Sign up to set email alerts
|

The GenomeAsia 100K Project enables genetic discoveries across Asia

Abstract: The underrepresentation of non-Europeans in human genetic studies so far has limited the diversity of individuals in genomic datasets and led to reduced medical relevance for a large proportion of the world's population. Population-specific reference genome datasets as well as genome-wide association studies in diverse populations are needed to address this issue. Here we describe the pilot phase of the GenomeAsia 100K Project. This includes a whole-genome sequencing reference dataset from 1,739 individuals of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
213
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 310 publications
(218 citation statements)
references
References 71 publications
4
213
1
Order By: Relevance
“…Without this representation, the success and benefits of genomic medicine will be disproportionately less. For this reason, efforts are being undertaken around the globe to produce BVDs for previously excluded populations recognizing that both affiliated policies and scientific infrastructure are required (29)(30)(31)(32).…”
Section: Reasons For Health Inequities In Genomic Medicine In Indigenmentioning
confidence: 99%
“…Without this representation, the success and benefits of genomic medicine will be disproportionately less. For this reason, efforts are being undertaken around the globe to produce BVDs for previously excluded populations recognizing that both affiliated policies and scientific infrastructure are required (29)(30)(31)(32).…”
Section: Reasons For Health Inequities In Genomic Medicine In Indigenmentioning
confidence: 99%
“…HLoF variants have also been identified in genes that affect disease risk (Karczewski et al, 2020), e.g., ACTN3, which is associated with ageing (Yang et al, 2003), HAO1, which is associated with kidney dysfunction (McGregor et al, 2020), and LRRK2, which is associated with Parkinson's disease (Whiffin et al, 2020). Similarly, in a recent analysis of 219 populations from 64 countries across Asia, it was reported that 43% of all proteincoding genes contain at least one protein-truncating variant, suggesting that HLoF variants can be well tolerated (Wall et al, 2019). In addition, a study of more than 500,000 human genomes examining 874 genes reported 13 individuals with disease-causing mutations in eight different genes, with two individuals carrying HLoF mutations leading to PTCs, although with no reported clinical manifestation of disease (Chen et al, 2016b).…”
Section: Is Transcriptional Adaptation Important In the Context Of Humentioning
confidence: 99%
“…Currently, the majority of DNA used for research studies come from participants of European descent, with only 2% of data contributed from African data sets (64). In response, a new pan-Africa biobank start-up, 54-gene (64) and additionally, the first pan-Asia biobank have launched (65), both with the aim of solving the problem of lack of global representation. Similar initiatives are found in Brazil (66).…”
Section: Lmic-based Data Repositories and Biobanksmentioning
confidence: 99%